Implementasi Kebijakan Standar Pelayanan Minimal Pendidikan Dasar di Dinas Pendidikan Kabupaten Sleman - Vitri, Oktaria; Kusumawiranti, Retno; Suwarjo, Suwarjo (POPULIKA, 2019)
The aim of this research is to find out and examine the implementation of basic minimum service standard (SPM) policies in the Sleman District Education Office. The type of research is qualitative descriptive research. Data collection techniques used are observation, interviews, and documentation. Analysis of the data with qualitative analysis. The implementation of policies related to the fulfillment of the Basic Education SPM which is the authority of the Sleman Regency Government has not yet reached 100%. In the indicator of basic education quality services from the side of access distance has been fulfilled while the indicators of study groups (rombel) have not been fulfilled. In the indicators of basic education quality services in terms of laboratory availability has not been fulfilled while the availability of teacher rooms already meets SPM standards. In basic education quality services in terms of teacher education qualifications, principals and supervisors have been fulfilled, but in terms of teacher qualifications the educator certified has not been fulfilled. Whereas the indicators for the realization of visits by supervisors to educational units are carried out once every month and each visit is carried out for 3 hours to carry out supervision and guidance not fulfilled. Therefore, in order to fulfill SPM Dikdas, it is best to: give sanctions to schools whose number of classes exceeds SPM, allocate funds with the SPM fulfillment priority scale, provide (support to teachers of PPG trainers) and optimize school supervisor performance.